Management of five root canals in mandibular first molar tooth: A case report - Daryono Daryono (Prima Journal of Oral and Dental Sciences, 2022)
The five root canals configuration is one of the abnormal morphology of molar teeth commonly found in the mandibular first molar. The treatment of mandibular first molar with five root canals, of which three were located in the distal root and two in the mesial root. A third canal was found between the distobuccal and distolingual root canals. Cleaning, shaping and filling the root canal system effectively is the basis of successful root canal treatment for aberrant canal configuration. The aim for this case report was present the importance of knowledge of the internal anatomy of five root canals for the success of endodontic treatment in mandibular first molar tooth. A 12 years old girl patient with dull pain in his right mandibular first molar since 5 days ago came to the Department of Conservative Dentistry and Endodontics, Trisakti Dental College and Hospitals. She left that his tooth has cavity since 2 years ago. Objective assessment showed a cavity extended to the pulp involving occlusal area (positive percussion test, negative palpation test). Radiographic examination showed cavity extended to the pulp with apical lesion and periodontal ligament widening on his right mandibular first molar tooth. A diagnosis of irreversible pulpitis with acute apical periodontitis was made for the mandibular right first molar. Pulpectomy treatment for 46 tooth was conducted. Endodontic success in teeth with the number of canals above that normally found requires a correct diagnosis and careful inspection. Morphological variations in pulpal anatomy must always be considered before beginning treatment. Although the incidence of root and canal variations is rare, every effort should be made to find and treat all canals for successful clinical results. Five root canals treatment of mandibular first molar tooth proven to be successful.